PhET Simulation Worksheet for Momentum and Impulse Learning Using the POE2WE Model - Ridho, Muhamad Aqil; Khusaini, Khusaini; Sunaryono, Sunaryono (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2024)
This study examines the feasibility and student responses to worksheets based on PhET simulations integrated with the POE2WE (Predict, Observe, Explain, Elaborate, Write, Evaluate) learning model for teaching momentum and impulse. The research employed a 4D development model and involved expert validators, practitioners, and 30 eleventh-grade students from a high school in Pasuruan. Data were collected using validation and student response questionnaires and analyzed descriptively. The results indicate that the developed worksheets were highly feasible for use in physics learning, as reflected in the validation score of 87.6%, categorized as "extremely feasible." Furthermore, student responses to the use of these worksheets during the learning process yielded a score of 89%, categorized as "practical." These findings suggest that integrating PhET simulations with the POE2WE learning model not only enhances the feasibility of the worksheets but also significantly supports the learning process by encouraging active participation and engagement among students. PhET simulations provide an interactive and visually appealing approach to understanding abstract physics concepts like momentum and impulse. Combined with the structured stages of the POE2WE model, the worksheets guide students to predict, observe phenomena, explain concepts, and evaluate their understanding systematically. This structured approach aligns with the needs of modern physics education, emphasizing inquiry-based learning and critical thinking skills. In conclusion, the integration of PhET simulations and the POE2WE learning model in worksheets demonstrates a highly effective and innovative strategy for teaching the concepts of momentum and impulse in physics. The combination of interactive simulations and the structured learning approach not only enhances students' engagement but also fosters a deeper conceptual understanding of the material. Furthermore, the high feasibility of implementation, coupled with overwhelmingly positive student responses, highlights its potential to significantly improve learning outcomes. This approach serves as a valuable resource for educators aiming to create dynamic and impactful learning experiences, ultimately contributing to the advancement of physics education.